Self-serving dictators - Geir B. Asheim; Leif Helland; Jon Hovi; Bjorn Hoyland (University of Oslo, Department of Economics, 2008)
We provide experimental evidence of self-serving fairness ideals in a dictator game design that includes treatments where funds can be transferred in two ways to the one player and in one way to the other. Two methods for transferring funds to the recipient produce the same results as the regular dictator game. However, two methods for transferring funds to the dictator reduce her generosity significantly. Hence, the fairness ideal adopted by dictators appears to be equal share per individual in the former case (as in the regular dictator game), and equal share per transfer method in the latter case.
Keywords: C91; D63; 330; Self-serving Bias; Experimental Economics; Dictator Game; Experimentelle Ökonomik; Gerechtigkeit; Eigeninteresse; Spieltheorie; Test